PERKEMBANGAN PEREKONOMIAN MASYARAKAT DESA BUMI JAYA KECAMATAN KAUBUN KABUPATEN KUTAI TIMUR - Toni Nurhadi Kumayza (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2013)
Trasmigrasi is a program to make the population distribution and equitable development. This study aimed to determine the placement of the background and social economic development in the village of village Transmigration Bumi Jaya sub Koubun Kutai Timur district.This research method, this phase 1 activities Heuristics collect traces of historical data related to economic development. 2 Critics of this stage, the critiques of the historical sources that the testing and assessment of the historical sources. 3 Interpretation of all of the facts and the data collected and arranged in chronological order, it can draw a conclusion or derived meanings of interrelated facts obtained. 4. After going through the stages heuristic historiography, criticism and interpretation, the authors conducted the last stage of the study of history is poured in a systematic, analytical and chronological with all his thoughts into writing a history paper. Within a few decades transmigration Participants perform interaction or socializing with other participants from outside the area or locals, they exchanged experiences go hand in hand doing various activities so that they get a sense of kinship with each other closely. Thus the problem is in the face will be resolved easily together and they know each other, they also do mixing culture with mixed marriages. Last transmigration areas in east Kutai district has experienced fairly rapid economic growth and promise as potential availability of land is developed for.